PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENGENDALIAN BIAYA DAN PENGUKURAN KINERJA PUSAT BIAYA - Bahia, Bahia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out and to analyze the implementation of responsibility accounting effective and efficient and in accordance with its function as cost control and research performance instrument. The research object is PT KASA HUSADA WIRA JATIM is a company which engages in the field of medical equipment factory. The research method is qualitative. Descriptive analysis technique has been applied by the researcher in order to describe what the research object exactly is. It has been found from the result of the research that company organization structure has shown responsibility centers. The budget preparation process has been carried out by using bottom up budgeting, but the responsibility center code has been shown yet and the separation between controllable and uncontrollable cost has not been performed yet. The responsibility report has been carried out by comparing the budget to the realization. It has been found from the result of performance evaluation which has been done by comparing the cost budget and the realization that the efficient manager is the production manager whereas the inefficient manager is the general affair and administration manager and sales manager. It can be concluded from the result of the analysis that by implementing the responsibility accounting system, top managers can conduct performance evaluation and cost control. In order to make the responsibility accounting system is said to be good when the use and the realization of the budget is in accordance with the prevailing standards.Keywords: Responsibility accounting, performance assessment, controllable and uncontrollable cost.